2013
DOI: 10.1038/ejhg.2013.279
|View full text |Cite
|
Sign up to set email alerts
|

VHL mosaicism can be detected by clinical next-generation sequencing and is not restricted to patients with a mild phenotype

Abstract: The identification of Von Hippel-Lindau (VHL) mosaic mutations by conventional Sanger sequencing requires a labour-intensive enrichment step, thus explaining that mosaicism occurrence is underestimated in patients. Nowadays, it is possible to detect mutation in cell sub-populations by next-generation sequencing (NGS). Here, we described a diagnosis strategy using NGS with high coverage in a series of eight patients who were negative for a VHL abnormality by Sanger sequencing and deletion search. In two patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 9 publications
1
27
0
Order By: Relevance
“…83,86 Detection of mosaicism is critical in terms of confirming a diagnosis and estimating the risk to siblings and offspring. 84,85 As next-generation sequencing replaces Sanger sequencing, mosaic cases may be more easily detected, which could provide the data needed to elucidate the true frequency of mosaicism in VHL.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…83,86 Detection of mosaicism is critical in terms of confirming a diagnosis and estimating the risk to siblings and offspring. 84,85 As next-generation sequencing replaces Sanger sequencing, mosaic cases may be more easily detected, which could provide the data needed to elucidate the true frequency of mosaicism in VHL.…”
mentioning
confidence: 99%
“…Generally, patients with mosaicism tend to be more mildly affected or asymptomatic, 83 although this is not always the case, and mosaicism has been confirmed in individuals with classic VHL disease as well. 84,85 It is now recommended that additional testing methods be used to rule out mosaicism in the parents of a patient with proband with a seemingly de novo mutation and in cases moderately or highly suspicious of VHL in whom standard testing methods have failed to detect a disease-causing mutation.…”
mentioning
confidence: 99%
“…Although the clinical information for that previous case was unknown, it was described as severe NM . Generally, the phenotype of mosaicism is milder than that of full mutations . The present patient was not thought to have severe NM.…”
mentioning
confidence: 71%
“…That might be because the present patient had a mosaicism. NGS should be the first method of choice to detect low‐grade mosaicism and determine its correct ratio . The ratio of mosaicism may predict outcome in patients with NM.…”
mentioning
confidence: 99%
“…A mosaic event refers to a situation wherein tissues or cell populations in a single individual have different genotypes; this can occur when a mutation arises during (fetal) development [76]. For example, Beicht et al [78] recently revealed a mosaic mutation in COLA5 in an individual with Alport syndrome, Tan et al [79] identified a mosaic PKD1 mutation in a patient with ADPKD, and Coppin et al [77] reported a mosaic VHL mutation in a patient with an early manifestation of von Hippel-Lindau disease. In addition, if the mutation is not present in the tissue from which DNA was extracted, the causative mutation may not be identified at all.…”
Section: Diseasementioning
confidence: 99%